Nanopartículas Auto-organizadas do Polissacarídeo Extraído de Sterculia striata (Goma do Chichá) Modificado com Anidrido Ftálico - Sombra, Venícios Gonçalves (2019)
From the perspective of polysaccharide application to produce nanoparticles for drug incorporation and release various modifications have been proposed for polysaccharide chains functionalization, producing more hydrophobic materials that could interact with hydrophobic drugs. Acylation reactions have been applied aiming polysaccharide hydrophobization for this purpose. Acylated derivatives were produced with phthalic anhydride and chichá gum varying gum:anhydride ratios in 1:6, 1:9 and 1:12. Nanoparticles were produced from these derivatives and the effect of purification of the acylated derivatives in the formation of nanoparticles formed by self-assembly by dialysis was evaluated. Hydrophobic materials were obtained through the insertion of phthalic groups on the polysaccharide structure, this modification was confirmed by infrared spectroscopy by the appearance of bands at 1604, 1580, 1490 and 1468 cm-1, characteristic of aromatic ring present on the of phthalic anhydride structure. After purification the acylation reaction residue was 14.8%, 23.0% and 51.2% for derivative CHFT 1:6, CHFT 1:9 and CHFT 1:12, respectively. Nanoparticles formed from the purified derivatives did not presented a decreasing in the polydispersity index (PdI) and a increasing in the particle diameter (d) with the concentration increasing. For nanoparticles formed from the purified derivatives the increase of derivative concentration lead to an increase in the polydispersity index. After purification were obtained nanoparticles smaller than those produced from unpurified derivatives to CHFTP 1:6 with higher values of zeta potential modulus, which implies a greater stability of these nanoparticles.Nanoparticles produced with CHFT 1:12 at 1.0 mg/mL, showed the smalest IPd (0.140) and size of 126.5 nm. Nanoparticles formed using CHFTP 1 :6 at 1.0 mg/mL showed the smalest IPd (0.200) and size of 299,3 nm.